Carbon footprint assessment and mitigation options of dairy under Chinese conditions: Implementation plan - Hongmin, Dong (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2018)
Presentation to the Chinese Academy of Agricultural Sciences (CAAS) 12 &16 October 2018, Beijing, China Presented by Dong Hongmin Ph.D, Institute of Environment and Sustainable Development in Agriculture (IEDA), Chinese Academy of Agricultural Sciences (CAAS)